2024
DOI: 10.36740/merkur202401115
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the dynamics of morbidity and mortality from hypertension in the Republic of Kazakhstan from 2010 to 2019

Yeldos Makhambetchin,
Aigerim Yessembekova,
Ardak Nurbakyttana
et al.

Abstract: Aim: The purpose of the research is to study trends in the dynamics of morbidity and mortality from arterial hypertension in the Republic of Kazakhstan for 2010-2019. Materials and Methods: Due to the interdisciplinary nature of the study, a set of methods was used: analytical, graph-analytical, statistical, sociological, clinical and economic analysis, organizational experiment. Results: The survey of 318 hypertension patients highlighted a common profile: hypertensive men aged 45-59, smokers, alcohol drinker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Furthermore, in the USA the number of maternal mortality cases grew with maternal age ( 43 ). A study from Kazakhstan reported that higher age associated with greater mortality risk in this period, and from 2019 to 2021 in Kazakhstan, there was a rise in mortality rates among women aged 35–39 from 0.48 to 4.37 per 100,000 individuals ( 48 , 49 ). Overall, even before the pandemic, obesity and high school non-completion were identified as important contributors to maternal mortality, while access to healthcare services and resources, family factors, such as revenue and education, and ecological determinants as poverty, gender inequality, human development also played a role ( 3 , 6 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the USA the number of maternal mortality cases grew with maternal age ( 43 ). A study from Kazakhstan reported that higher age associated with greater mortality risk in this period, and from 2019 to 2021 in Kazakhstan, there was a rise in mortality rates among women aged 35–39 from 0.48 to 4.37 per 100,000 individuals ( 48 , 49 ). Overall, even before the pandemic, obesity and high school non-completion were identified as important contributors to maternal mortality, while access to healthcare services and resources, family factors, such as revenue and education, and ecological determinants as poverty, gender inequality, human development also played a role ( 3 , 6 , 50 ).…”
Section: Discussionmentioning
confidence: 99%